Saturation Mutagenesis for Phenylalanine Ammonia Lyases of Enhanced Catalytic Properties - Tomoiagă, Raluca Bianca (Biomolecules, 2020)
Phenylalanine ammonia-lyases (PALs) are attractive biocatalysts for the stereoselective synthesis of non-natural phenylalanines. The rational design of PALs with extended substrate scope, highlighted the substrate specificity-modulator role of residue I460 of Petroselinum crispum PAL. Herein, saturation mutagenesis at key residue I460 was performed in order to identify PcPAL variants of enhanced activity or to validate the superior catalytic properties of the rationally explored I460V PcPAL compared with the other possible mutant variants. After optimizations, the saturation mutagenesis employing the NNK-degeneracy generated a high-quality transformant library. For high-throughput enzyme-activity screens of the mutant library, a PAL-activity assay was developed, allowing the identification of hits showing activity in the reaction of non-natural substrate, p-MeO-phenylalanine. Among the hits, besides the known I460V PcPAL, several mutants were identified, and their increased catalytic efficiency was confirmed by biotransformations using whole-cells or purified PAL-biocatalysts. Variants I460T and I460S were superior to I460V-PcPAL in terms of catalytic efficiency within the reaction of p-MeO-Phe. Moreover, I460T PcPAL maintained the high specificity constant of the wild-type enzyme for the natural substrate, l-Phe. Molecular docking supported the favorable substrate orientation of p-MeO-cinnamic acid within the active site of I460T variant, similarly as shown earlier for I460V PcPAL (PDB ID: 6RGS).